PENERAPAN MODEL KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 008 SIPANG - Herman '; Otang Kurniaman; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study, entitled Implementation of Model Cooperative Numbereds type Heads Together (NHT) To Improve Outcomes Science Learning Student Class V SD Negeri 008 Sipang. This study aims to improve learning outcomes fifth grade science students of SD Negeri 008 Sipang. The method used is the method of classroom action research (PTK) which is implemented in the second semester of the 2015/2016 academic year. The research sample is 20 students. The results obtained from the study average results of study before action 66.50 with a percentage of 40% increased to 65% with an average of 74 in cycle I. In the second cycle increased to 90% with an average of 83. Activities teachers in cycle the first meeting I earn a percentage of 62.50% with a good category, at the second meeting with a percentage increase of 75.00% in both categories. Furthermore, the first meeting of the second cycle of teacher activity also increased with the percentage of 84.37% is very good category and at the second meeting of the second cycle increased again with a percentage of 90.62% is very good category. Activities of students in the first cycle of the first meeting of the percentage of 56.25% gain enough categories, at a second meeting has increased by 65.62% the percentage of both categories, in this cycle the students begin to understand the learning activities by implementing cooperative learning model Numbered Heads Together characterized by activity students in the second cycle the first meeting with a percentage of 78.12% increased both categories. At the second meeting of the second cycle increased with the percentage of 84.37% sangatbaik category. The results of the study in class V SD Negeri 008 Sipang prove that the implementation of cooperative learning model Numbered Heads Together to improve learning outcomes fifth grade science students of SD Negeri 008 Sipang.Keywords: Numbered Heads Together, learning outcomes IPA